RNA Isolation from Purified Rice Necrosis Mosaic Virus Particles - , Sopan Ganpatrao Wagh; , Manoj Baliram Pohare; , Abhijit Arun Daspute; , Hanumant Baburao Wadekar; , Sachin Ashok Bhor (Archives of Current Research International, 2020)
Rice, particularly grows in tropical and subtropical areas, is one of the most important crops worldwide. Rice necrosis mosaic virus (RNMV) was first reported in Japan and causes necrotic lesions on leaf and yellowing. This virus has been classified as member of the Potyviridae family's Bymovirus genus. The fungus, Polymixa graminis, transmits RNMV. In this study, the methodology first explained RNMV virus particle - purification by ultra-centrifugation along with sucrose and cesium chloride gradient is described. Further, confirmation of purified RNMV particles under the electron-microscope is discussed. In the last RNMV RNA isolation from the purified RNMV particles were explained.